The manager’s decision in acknowledging and disclosing environmental liability: A Behavioral Model - Susi Sarumpaet (Universitas Hayam Wuruk Perbanas, 2016)
This study analyzes why managers accrue and disclose environmental liability, which involves managers’ discretions. Using the framework of the Theory of Planned Behavior (Ajzen 1991), this research hypothesizes that a manager’s intention to accrue and disclose environmental liability is influenced by: (1) attitudes (2) subjective norms, and (3) perceived behavioral control of the manager towards accruing and disclosing such information. The data was collected through a survey, employing a questionnaire modified from Weidman (2002). Responses from 50 corporate managers in Lampung Province were analyzed using structural equation model software package SmartPLS. This study finds that a manager’s attitude towards environmental liability is positively associated with his/her decision to accrue and disclose environmental liability. However, there is no evidence that subjective norms and behavioral control are associated with such a decision. An additional test using attitude as a moderating variable provides evidence that both subjective norms and perceived control behavior are positively associated with the attitude towards environmental liability.